PENGARUH KURS, EMAS, MINYAK TERHADAP HARGA SAHAM DENGAN INFLASI SEBAGAI VARIABEL INTERVENING - Fitri Yusnita; Indah Khairunnisa; Peny Cahaya Azwari (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2023)
The value of stocks is affected by a variety of factors, including changes in exchange rates, swings in the price of gold and oil, and fluctuating levels of inflation. These factors also contribute to market volatility. This study's objective is to investigate the factors that have an effect on stock prices, including inflation, the rate of the rupiah currency, and worldwide prices for gold and oil. Purposive sampling is utilized in conjunction with secondary data as the analytical instrument. According to the data that has been presented in this article, there is a statistically significant and negative relationship between the exchange rate and gold prices; there is also a statistically significant and similar relationship between gold prices and stock prices; there is no statistically significant relationship between stock prices and global oil prices; and there is a statistically significant and positive relationship between stock prices and inflation. Both the positive impact of exchange rates on stock prices and the negative influence of gold prices on stock prices are mediated by inflation. Conversely, gold prices have a positive influence on stock prices. Additionally, the price of oil on international markets has a considerable and positively significant impact on inflation. There is a correlation between the price of oil and the value of the stock market, but inflation is not a moderating factor in this relationship. Keywords: Kurs, Gold, Oil, Stock Price, Inflation